Let's assume the mass of bag A is x kg.
Then the mass of bag B is 2x + 3 kg.
Therefore, the total mass of both bags is x + (2x + 3) = 27 kg.
Simplifying the equation, we get 3x + 3 = 27.
Subtracting 3 from both sides of the equation, we get 3x = 24.
Dividing both sides of the equation by 3, we get x = 8.
Therefore, the mass of bag A is 8 kg, and the mass of bag B is 2(8) +3 = 16 + 3 = <<16+3=19>>19 kg. Answer: \boxed{8, 19}.
A customer is buying two bags of potatoes, bag A and bag B. The mass of bag B is 3 kg more than twice the mass of bag A. The total mass of both bags of potatoes is 27 kg. Determine the mass of each bag of potatoes.
1 answer